Pembuatan Aalat Peraga Kiara Payung dalam Pembelajaran Sistem Tata Surya - Slamet Slamet (Jurnal Penelitian Pembelajaran Fisika, 2019)
The props "Kiara Payung" are a tool in learning the Solar System. This props is a unit of several components of props that can visualize various phenomena such as rotations and revolutions of the earth and moon, solar and lunar eclipses, tides of seawater, position of celestial bodies in their orbits, and artificial satellite motion. Named "Kiara Payung" because the components of the model of the solar system phenomenon are integrated to form a shade tree "Kiara Payung" which is planted in the school environment. While the word "Payung" to remind that the framework of used umbrellas as one of the materials for making props. The purpose of the use of teaching aids is to concretize the material of the solar system as well as to improve student learning outcomes. The effort to concretize the material is done by modeling the teaching aids in the classroom, while to find out the improvement in student learning outcomes is used the test method. The test is conducted twice at the end of each subject. Test data retrieval is focused on the VI C, which has always been lower than other class VI. Learning outcomes show that by using the props "Kiara Payung" students' understanding of the material of the solar system is better. In addition, there is an increase in student learning outcomes. As many as 34 students in grade VI C, in the first test learning completeness only reached 73,6% and in the next test it increased to 91,2%